Studi Numerik Upwelling di Daerah Perairan Kalimantan Timur - Maulana, Restu Agesta Dwi; Yusuf, Mustaid; Perwitasari, Devina Rayzy (GEOSAINS KUTAI BASIN, 2021)
The aim of this study is to predict the potential upwelling areas around East Kalimantan Waters, based on vertical current velocity, temperature, and salinity information through the COHERENS (A Coupled Hydrodynamical-Ecological Model for Regional and Shelf Seas) simulation, a three-dimensional hydrodynamic model. The model was performed simulation for one year period (1st January – 31th December 2016). Four major tidal constituents (M2, S2, K1, O1) and wind speed have used as generating force. The simulation results showed the upwelling areas as well as downwelling. The upwelling area located mostly in the southern parts of the Makassar Strait while only a few areas located in the vicinity of the East Kalimantan coastline.